Cataloging Digitized Continuing Resources in a Shared Record Environment. Issue 2 (17th February 2018) - Han, Myung-Ja K.; Carlstone, Jamie; Harrington, Patrick
ABSTRACT: Cataloging digitized continuing resources is a challenging task for many libraries because of their complex cataloging rules and characteristics of format. As libraries provide their digitized content and catalog records in shared environments, like HathiTrust, and use them as an access point, libraries also have to work with holdings and item records created by each contributing institution's local practice. This article discusses common challenges imposed on libraries when creating and providing access to digitized continuing resources available in a shared environment, stresses the importance of having shareable holdings and items records, and suggests possible ways to work with those challenges.